Cluster Country Program Evaluation on Small States : Seychelles Country Case Study, Enhancing Competitiveness and Private Sector Development - Charlier, Florence (World Bank, Washington, DC, 2016)
Between 1976 and the mid-2000s, Seychelles had transformed itself from a poor subsistence economy into a high middle income country with low levels of poverty and many social indicators comparable to Organisation for Economic Co-operation and Development (OECD) countries. However, this growth could not be sustained and faced with a growing international financial crisis, severe shortages of foreign exchange resulted in the government defaulting in its international payment obligations in 2008. Starting that year, the government began implementing a radical program of macroeconomic stabilization and structural reforms. The centerpiece of these reforms was a strong fiscal adjustment to reduce the burden of external debt and a progressive dismantling of the role of the state in allocating resources. These reforms were supported by the Standby and Extended Fund Facility (EFF) arrangements of the International Monetary Fund (IMF), and by the Bank through a series of development policy loans (DPLs). Seychelles also benefited from debt relief provided by other official and private international creditors. As a result of the reforms, macroeconomic imbalances were corrected, the role of markets was enhanced, and economic growth restored. However, some important measures such as privatization or SOE reforms (to improve their governance) were stalled or progressing at a very slow pace and there are increasing pressures to reverse some key reforms (such as reducing the size of government). The Bank played an important role in Seychelles’ successful turn-around.